Lotus. The first thirty years of an architectural magazine - Mauro Marzo (Festival dell'Architettura Magazine, 2018)
Imagined more as an annual dedicated to the best works of architecture, urban and industrial design, during the first seven issues, the magazine «Lotus» shifts the axis of its purpose from that of information and professional updating to one of a critical examination of the key issues intrinsic to the architectural project. This article identifies some themes, which pervaded the first thirty years of «Lotus» life, from 1964 to 1994, re-emerging, with variations, in many successive issues. If the monographic approach set a characteristic of the editorial line that endures over time, helping to strengthen the magazine’s identity, the change in the themes dealt with over the course of the decades is considered as a litmus test of the continuous evolution of the theoretical-design issues at the core of the architectural debate.